2021
DOI: 10.7554/elife.64283
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of translation in yeast cells impaired for ribosome recycling favors short, efficiently translated mRNAs

Abstract: In eukaryotes, 43S preinitiation complex (PIC) formation is a rate-determining step of translation. Ribosome recycling following translation termination produces free 40S subunits for re-assembly of 43S PICs. Yeast mutants lacking orthologs of mammalian eIF2D (Tma64), and either MCT-1 (Tma20) or DENR (Tma22), are broadly impaired for 40S recycling; however, it was unknown whether this defect alters the translational efficiencies (TEs) of particular mRNAs. Here, we conducted ribosome profiling of a yeast tma64∆… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 80 publications
4
33
0
Order By: Relevance
“…Previously, we observed this same pattern of translational reprogramming in yeast cells impaired in different ways for assembly of 43S preinitiation complexes (PICs), including: (i) increased phosphorylation of eIF2 α in WT cells induced by isoleucine/valine starvation using the drug sulfometuron (SM), which decreases formation of the eIF2-GTP-Met-tRNA i ternary complex required to assemble 43S PIC; (ii) deletion of genes TMA64 and TMA20 encoding factors that recycle 40S subunits from termination complexes at stop codons to provide free 40S subunits for PIC assembly; and (iii) a reduction in free 40S subunits by depleting a 40S subunit protein. This recurrent pattern of translational reprogramming could be explained by proposing that increased competition for limiting PICs allows “strong” mRNAs, highly efficient in recruiting PICs, to outcompete weak mRNAs that recruit PICs less efficiently (Gaikwad et al 2021). Supporting the possibility that a similar competition exists among mRNAs translationally altered by dcp2 Δ, we found that the TE_up_ dcp2 Δ group of mRNAs also shows an increased median TE in response to increased phosphorylation of eIF2 α induced by SM (WT_SM) and by deletion of TMA64/TMA20 ( tma ΔΔ), whereas the TE_dn_ dcp2 Δ mRNAs exhibit the opposite changes in median TE in response to these two conditions (Figure 5 – figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we observed this same pattern of translational reprogramming in yeast cells impaired in different ways for assembly of 43S preinitiation complexes (PICs), including: (i) increased phosphorylation of eIF2 α in WT cells induced by isoleucine/valine starvation using the drug sulfometuron (SM), which decreases formation of the eIF2-GTP-Met-tRNA i ternary complex required to assemble 43S PIC; (ii) deletion of genes TMA64 and TMA20 encoding factors that recycle 40S subunits from termination complexes at stop codons to provide free 40S subunits for PIC assembly; and (iii) a reduction in free 40S subunits by depleting a 40S subunit protein. This recurrent pattern of translational reprogramming could be explained by proposing that increased competition for limiting PICs allows “strong” mRNAs, highly efficient in recruiting PICs, to outcompete weak mRNAs that recruit PICs less efficiently (Gaikwad et al 2021). Supporting the possibility that a similar competition exists among mRNAs translationally altered by dcp2 Δ, we found that the TE_up_ dcp2 Δ group of mRNAs also shows an increased median TE in response to increased phosphorylation of eIF2 α induced by SM (WT_SM) and by deletion of TMA64/TMA20 ( tma ΔΔ), whereas the TE_dn_ dcp2 Δ mRNAs exhibit the opposite changes in median TE in response to these two conditions (Figure 5 – figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
“…3) for the 1200 mRNAs belonging to the same two groups analyzed in (B) for which data was available in all three analyses (excluding a few outliers with log2∆TE values > +4 or < -4). In panels A-B, ribosome profiling data from (Gaikwad, Ghobakhlou et al 2021) 1 x 10 -6 1 x 10 -6 8 x 10 -6 1 x 10 -5 1 x 10 < 10 -14 < 10 -14 1 X 10 -14 1 X 10 -12 4 X 10 -11 6 X 10 -7 1 X 10 -6 1 X 10 -6 2 X 10 -6 4 X 10 -6 6 X 10 -6 8 X 10 -6 2 X 10 -5 2 X 10 -5 3 X 10 -5 5 X 10 -5 5 X 10 3 x 10 -10 4 x 10 -9 2 x 10 -7 2 x 10 -7 2 x 10 -6 5 x 10 -6 8 x 10 -5 8 x 10 -5 9 x 10 6 X 10 -13 3 X 10 -10 7 X 10 -10 6 X 10 -9 2 X 10 -8 6 X 10 4 X 10 -9 6 X 10 -8 7 X 10 -7 2 X 10 -6 2 X 10 -5 4 X 10 -5 7 X 10 -5 7 X 10 2 X 10 -13 9 X 10 -7 1 X 10 -6 1 X 10 -6 4 X 10 -6 5 X 10 -6 4 X 10 -5 7 X 10 -5 9 X 10 -5 9 X 10…”
Section: Figure 3 -Source Datamentioning
confidence: 99%
“…Three of six clusters were disproportionately enriched with GO terms related to the translation machinery containing one‐third of all 135 ribosomal proteins (RPs) in yeast (Gaikwad et al, 2021 ). Cluster 4 increased steadily over the first 40 min.…”
Section: Resultsmentioning
confidence: 99%
“…[11,62] In addition, the yeast proteins do not appear to have a particular role in promoting reinitiation at uORF stop codons, as they do in human cells. [85] It has also been shown that an unrecycled 80S ribosome can reinitiate translation in yeast, although the mechanism of this process is less clear. Unlike 40S reinitiation, reinitiation by an 80S ribosome does not require an AUG codon and generally occurs without obvious preference for codon in the 3′UTR.…”
Section: Reinitiation and Regulation Of Gene Expression By Uorfs And ...mentioning
confidence: 99%
“…Reduced ribosome supply is known to skew the distribution of mRNA translation efficiencies by amplifying the relative production of proteins from genes that are most capable of recruiting ribosomes. [82,85,86] An additional mechanism by which dORF translation could affect cellular homeostasis is if the peptide products themselves have functional roles. For example, peptides derived from dORFs have been observed bound to MHC complexes on the cell surface in an apparently immunogenic role.…”
Section: Reinitiation and Regulation Of Gene Expression By Uorfs And ...mentioning
confidence: 99%